IMPLEMENTASI PROGRAM SEKOLAH RAMAH ANAK SUATU KEBIJAKAN DALAM PEMENUHAN HAK ASASI ANAK (STUDI PADA 3 SEKOLAH DI KOTA PEKANBARU) - Neri Widya Ramailis; Putri Mhelsy; Hidayati Hidayati; Kadek Surningsih (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This paper discusses the implementation of child-friendly schools towards fulfilling children's rights at 3 levels of schools in Pekanbaru. The purpose of this research is to find out how each school implements child-friendly schools to fulfill children's rights. The theory used is the theory of criminal policy which in this theory explains how a policy is carried out to prevent criminal politics from occurring. This research is based on the results of using the Mix Methode method, namely quantitative and qualitative, to get the result that all schools that were sampled from this study have fulfilled the rights of children in implementing child-friendly schools, this is indicated by the results of 46.8% stating that they get their rights fulfilled from implementation of child-friendly schools implemented by their schools.